Pathophysiology of disease : an introduction to clinical medicine - McPhee, Stephen J (Prentice-Hall International, 1995)
This concise review of pathophysiology presents each disease as disordered physiology. Organized by organ system, each chapter discusses normal structure and function, pathology, and disordered physiology, common clinical presentations and mechanisms underlying symptoms and signs.
Keywords: patologie; PATOFYZIOLOGIE